Advances in the therapy of Alzheimer's disease: targeting amyloid beta and tau and perspectives for the future. (January 2014) - Hampel, Harald; Schneider, Lon S; Giacobini, Ezio; Kivipelto, Miia; Sindi, Shireen; Dubois, Bruno; Broich, Karl; Nisticò, Robert; Aisen, Paul S; Lista, Simone
<x xml:space="preserve">Abstract</x> Worldwide multidisciplinary translational research has led to a growing knowledge of the genetics and molecular pathogenesis of Alzheimer's disease (AD) indicating that pathophysiological brain alterations occur decades before clinical signs and symptoms of cognitive decline can be diagnosed. Consequently, therapeutic concepts and targets have been increasingly focused on early-stage illness before the onset of dementia; and distinct classes of compounds are now being tested in clinical trials. At present, there is a growing consensus that therapeutic progress in AD delaying disease progression would significantly decrease the expanding global burden. The evolving hypothesis- and evidence-based generation of new diagnostic research criteria for early-stage AD has positively impacted the development of clinical trial designs and the characterization of earlier and more specific target populations for trials in prodromal as well as in pre- and asymptomatic at-risk stages of AD.